Screening of plant collection of Cibodas Botanic Gardens, Indonesia with anticancer properties - Risha Pratiwi; Yati Nurlaeni (Society for Indonesian Biodiversity, 2020)
Abstract. Pratiwi RA, Nurlaeni Y. 2020. Screening of plant collection of Cibodas Botanic Gardens, Indonesia with anticancer properties. Biodiversitas 21: 5186-5229. Cancer is a life-threatening disease worldwide. One approach to developing effective treatment in fighting cancerous cells is to obtain anticancer drug candidates from natural resources, such as plants. This study aimed to inventory and categorize plant collections in Cibodas Botanic Gardens (CBG), West Java, Indonesia that has anticancer properties in a detailed and comprehensive manner. Literature research was conducted in international scientific databases using several keywords expressing anticancer properties to produce list of plant species potential for anticancer. The results of this research were then cross-checked with the plant collection database of CBG. List of plants exhibits anticancer activities were then categorized based on the IC50 values (an indicator of cytotoxicity). Our result showed 291 species from 90 families of CBG plant collection harbor anticancer properties. Among them, 93, 100, 36, and 62 species have IC50 values under Class I (strong), Class II (moderate), Class III (inactive), and Class IV (insufficient IC50 data), respectively. The families with the highest number of potential anticancer plants are Lauraceae, Leguminosae, Meliaceae, Myrtaceae, Moraceae, Cupressaceae, Asparagaceae, Euphorbiaceae, Compositae, Clusiaceae, Lamiaceae, Apocynaceae, Adoxaceae, Amaryllidaceae, and Elaeocarpaceae. Species that have strong anticancer activities include Acacia farnesiana, Aglaia edulis, A. elliptica, A. silvestris, Artocarpus elasticus, Bauhinia strychnifolia, Buxus microphylla, Calophyllum soulattri, Cerbera manghas, Cocculus orbiculatus, Cryptocarya chinensis, C. konishii, C. laevigata, Dalbergia parviflora, Diospyros discolor, Erythrina abyssinica, Etlingera elatior, Ficus fistulosa, Garcinia x mangostana, Hemerocallis fulva, Jatropha gossypiifolia, Panax ginseng, Podocarpus macrophyllus, Psidium cattleianum, Sansevieria ehrenbergii, Tacca chantrieri, Toona sinensis, Viburnum odoratissimum, and V. Sambucinum. Even Serenoa repens and Taxus sumatrana contain active compounds that have been commercialized as anticancer drugs. The data resulted from this study can serve as baseline information for further research in drug discovery and development for anticancer treatments using living plant specimens collected in CBG. CBG has a great prospect of medicinal plants that require further studies for formulating anticancer drug as an alternative natural resource.